Validity and reliability of a standardized protocol for assessing the one repetition maximum performance during overhead pressing exercises - Soriano, M. A.; García-Ramos, A.; Torres-González, A.; Castillo-Palencia, J.; Ayuso, V.; Marín, P. J.; Comfort, P. (The Journal of Strength and Conditioning Research, 2021)
The aim of this study was to determine the validity of performing 3 one repetition maximum (1RM) assessments for the push press (PP), push jerk (PJ), and split jerk (SJ) in sequence in one testing session vs. the criterion method (testing on separate days), while determining the between-session reliability of the combined assessment. Twenty-two well-trained men (n = 22; age: 28.5 + 1.3 years; height: 1.80 + 0.04 m; body mass: 84.9 + 1.9 kg; training experience: 4.27 + 4.08 years) participated in this study. The 1RM was assessed in a sequential order in the same testing session (combined 1RM assessment) for the PP, PJ, and SJ on 2 occasions, to determine between-session reliability. The 1RM for each exercise was also examined on 3 separate sessions to compare the results against the combined method. A high reliability, low variability, and low measurement error were evident for the PP (intraclass correlation coefficient [ICC] = 0.960; coefficient of variation [CV] = 1.8%; smallest detectable difference [SDD] = 7.1%), PJ (ICC = 0.978; CV = 1.5%; SDD = 5.4%) and SJ (ICC = 0.987; CV = 0.8%; SDD = 4.6%). In addition, there were no significant (p > 0.05) or meaningful (Eta2 =0.001) differences between the single and combined assessments. The high reliability and validity of the combined assessment suggest that practitioners and researchers may simplify the testing procedure by assessing the 1RM during the 3 main overhead pressing exercises in a single testing session.